Pengaruh Penambahan Tepung Tulang Sotong (Cuttelfish bone) dalam Ransum terhadap Konsumsi Pakan, Pertambahan Bobot Badan, dan Karkas Ayam Pedaging - Damaryanto Widharto; W. Marsudi (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2017)
AbstractThis research was conducted to to know influence of cuttlefish bone flour in ransum to feed consumption, average daily gain,  and carcasse weight. The research use 60 day old chick of broilers which were devided into 4 treatments, that is 1) control treatment (T-0), broiler were given concentrate feed without addition of cuttlefish bone flour, 2) T-1, broiler were given concentrate feed with addition of cuttlefish bone flour as much as 1%, 3) T-2, broiler were given concentrate feed with addition of cuttlefish bone flour as much as 1.5%, and 4) T-3, broiler were given concentrate feed with addition of cuttlefish bone flour as much as 2%.The variables observed feed consumption, average daily gain,  and carcasse weight. The result showed that feed consumption is 54.59 (T-0), 55.71 (T-1), 58.77 (T-2),  58.55 g/head/day (T-3), average daily gain is 38.8 (T-0), 41.5 (T-1), 40.6 (T-2) and  38.7 (g/head/day T-3), and carcasse weight 531.33 (T-0), 750.67 (T-1), 761.67 (T-2),  770.67 g/head/day (T-3). Research conclusion  is addition of cuttlefish bone flour in ration not yet to improve feed consumption, and average daily gain, but can improve carcasse weight of broiler.Keywords : Broiler, carcasse, and cuttlefish bone flour.